Perancangan Sistem Ujian Berbasis Komputer - Vista, Umar Faruq; Juniawan, Fransiskus Panca; Zaliman, Iski (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
In the digital age, the use of information technology is felt in almost all areas such as healthcare, banking, culture and education. In the world of education, the application of information technology is indispensable both in teaching and learning activities and in student assessment. In the assessment of exams on campus, exams are generally used in which professors distribute test questions and students answer questions posed by lectures on a piece of paper has been provided. With regular exams, this often causes problems such as lectures being behind in grading report cards because teachers have to correct each student's answer. Exam Information System is a web-based online system that can help provide solutions to problems related to student assessment. In creating web-based test information system using waterfall approach including analysis, design, coding and testing along with entity relationship diagrams in database design. With the existence of a web-based exam information system, teachers can more easily process valuable student data to generate valuable reports more efficiently and effectively more fruitful. Keywords : Information system, online exam, waterfall method, computer, designing.